A survey of the safety conditions of student housings: A case study in a type one university in Shiraz, Iran - Mehdi Jahangiri; Parvaneh yekzamani; Seyedeh Fatemeh Ahmadi; Bahare Mahmoudabadi; Fariborz Behbood; Mahdieh Delikhoon; Korosh Azizi (Shiraz University of Medical Sciences, 2017)
Objectives: This study aimed to investigate the extent of implementation of safety measures in 14 student housings in one of the largest universities in Fars province, Shiraz, Iran. Method: A cross-sectional study was conducted in 14 student housings of one of the largest universities, located in Shiraz, Iran. Audit checklists were completed and rated thought field inspection and interview. Safety Requirement Index (SRI) was then used to evaluate the safety of student housings. SRI was graded on five scales (0-19%: very poor (unsafe); 20-39%: poor (relatively unsafe); 40-59%: moderate; 60-79%: good (relatively safe): and 80-100%: excellent (safe). Results: The mean SRI score was 71.01±15.46%. The highest and lowest level of SRI was 94.11±6.60% for dimensions of public health (and 47.70±18.42% for elevator safety. Conclusion: None of the studied housings was completely safe in all dimensions. Most of the studied housings were categorized as safe in the dimensions of public health and ventilation and air-conditioning systems; relatively safe in the dimensions of electrical, building, fire and kitchen safety; and moderate in the elevator safety and emergency response. Establishment of safety management system is necessary to promote safety in the studied housings. The results of this study indicated the need to inform the authorities about the safety priorities in housings, to promote the safety conditions. The results could also be used to raise awareness regarding their role and responsibilities about the safety of housings.